Bayang-Bayang Lombroso: Epigenetika dan Kembalinya Pendekatan Biologis dalam Hukum Pidana - Zul Khaidir Kadir (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Criminal law based on genetic determinism was once rejected in modern criminal law systems because it was deemed contrary to the principle of individual responsibility. However, the rise of epigenetics and neurocriminology in contemporary legal practice indicates a reconstitution of the biological basis for attribution of criminal culpability. This study aims to analyze the extent to which developments in epigenetics reopen opportunities for the operation of biological approaches in criminal law, while also critiquing the conceptual dangers they pose to the principles of justice and moral responsibility. The research method uses a normative legal approach with a conceptual approach. The results show that epigenetics works as a tool for scientific validation of the formation of risk categories in criminal law, while simultaneously weakening the perpetrator's position as a moral subject. The criminal law structure that technocratically accepts biological arguments creates a new form of legal exclusion through medical classifications that are not open to ethical evaluation. In this situation, the law operates as an instrument of biological management of bodies deemed deviant. The position of neurocriminology in this case is no longer merely a tool, but rather the center of the configuration of biolegal power that defines responsibility based on predisposition, not will. Therefore, a new normative framework is needed that can uphold the principle of individual responsibility while rejecting the ethical reduction of biological diagnoses in the criminal law system.